Separation of cetirizine enantiomers by capillary electrophoresis with a dual selector system based on borate-glucose complexes and sulfated-β-cyclodextrin - Švecová, Petra; Petr, Jan (Talanta, 2019)
The aim of this study was to focus on the reduction of chiral selector concentration, sulfated-β-cyclodextrin, in an attempt decrease the running costs associated with separating cetirizine enantiomers by capillary electrophoresis. The decrease in the concentration of chiral selector was achieved by adding D-glucose to the background electrolyte, which consisted of sodium borate. Optimal separation of cetirizine enantiomers was obtained in the electrolyte containing 500 mmol L-1 borate pH 9.5 with 1.0 mg mL-1 sulfated-β-cyclodextrin, and 1000 mmol L-1D-glucose. This means a 15-fold reduction in the concentration of sulfated-β-cyclodextrin. The mechanism of the separation in this electrolyte was investigated using direct injection mass spectrometry. The electrolyte of borate, D-glucose, and sulfated-β-cyclodextrin forms a dual selector system, in which one selector is represented by the sulfated-β-cyclodextrin and the second selector is represented by the D-glucose-borate complexes.